BROADBAND RECTANGULAR HORN ANTENNA WITH DIELECTRIC LENS FOR POINT-TO-POINT WIRELESS COMMUNICATION - Semenov, A. O.; Semenova, O. O.; Pinaiev, B. O.; Kulias, R. O.; Krystoforov, A. V. (Systems and Technologies, 2022)
Modern information technologies are developing rapidly. The application of the Internet of Things and sensor networks requires the development of new frequency ranges. At the same time, there is a tendency for rapid transition from the decimeter range to the centimeter range of wavelengths. Today, there is an urgent scientific and practical task of creating new antenna devices for use in wireless information communication and sensor networks with point-to-point wireless communication. Antennas are an extremely important component of wireless information communication and sensor network devices. To ensure high-quality wireless communication, an important role is played by the shape of the amplitude pattern, which determines the directional properties of the antenna. The level of information signals and the possibility of spatial separation of channels depends on the quality of the antenna parameters agreement in the operating frequency range. Also, the energy efficiency of information communication devices significantly depends on the magnitude of the directional properties of the antenna. The object of research in the paper is the process of electromagnetic wave radiation and directional properties of a rectangular horn antenna with a dielectric lens in single-mode operation. The proposed broadband rectangular horn antenna with a dielectric lens has a classic geometric configuration and operates in the frequency band 4285.7 MHz – 8571.4 MHz. Its dimensions are width 318 mm, height 240 mm, length 320 mm. The antenna is excited by a probe exciter in the form of an asymmetric pin. The antenna is powered by a coaxial cable with a wave resistance of 75 Ohms. In addition to the basic H10-type wave, many higher types of electromagnetic waves are excited near the pin. All excited higher types of waves are in the closed mode of operation of the rectangular waveguide and decay exponentially as they propagate to the horn. Their amplitude decreases more than 100 times. Therefore, higher types of waves do not pass through the throat of the horn and do not reach the opening of the horn in which the dielectric lens is located. As a result of research, it was established that in the operating frequency range of 6.5 GHz ... 7.6 GHz, the width of the antenna’s directional pattern varies within the following limits: 2θE 0.5 = 8.14º...9.75º; 2θH 0.5 = 6.2º...7.2º. The coefficient of directional action of the antenna in the working frequency range is within 490-370 times, and its power gain varies within 26.55-26.0 dB.